2017
DOI: 10.1016/j.psychsport.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The quiet eye supports error recovery in golf putting

Abstract: Objectives: The aim of this study was to further examine the relationship between the Quiet eye (QE, Vickers, 1996) and performance. We aimed to scrutinise the relationship between QE and shot outcome and replicate the robust relationship between QE and expertise. Based on recent findings (Cooke et al., 2015) showing that motor planning is dependent upon the outcome of a previous attempt, we wanted to examine the influence of prior performance on the functionality of the QE. Design: We performed a 2 (expertise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…As expected, larger thresholds yielded 3 longer quiet eye durations, in line with the findings reported in a previous multiple-threshold EOG 4 study . Moreover, these quiet eye durations are consistent with those obtained 5 using camera-based eye tracking in a similar sample (e.g., Walters-Symons, Wilson, & Vine, 2017).…”
Section: Quiet Eye and Eye Quietness 22supporting
confidence: 88%
See 1 more Smart Citation
“…As expected, larger thresholds yielded 3 longer quiet eye durations, in line with the findings reported in a previous multiple-threshold EOG 4 study . Moreover, these quiet eye durations are consistent with those obtained 5 using camera-based eye tracking in a similar sample (e.g., Walters-Symons, Wilson, & Vine, 2017).…”
Section: Quiet Eye and Eye Quietness 22supporting
confidence: 88%
“…In the case of golf putting, the quiet eye period has been defined as the duration of the final ocular fixation on the ball, with onset prior to the initiation of the swing movement and offset when the gaze deviates from the ball, potentially even after putter-ball impact (Vickers, 2007). Longer quiet eye durations have been reported for experienced versus novice golfers (Walters-Symons, Wilson, & Vine, 2017) and for holed versus missed putts in experienced golfers (Wilson & Pearcy, 2009).…”
mentioning
confidence: 93%
“…Two noteworthy examples of experimental studies that could guide future research, were carried out by Gray and Allsop (2013) and Walters-Symons, Wilson, and Vine (2017). Gray and Allsop (2013) found that pressurized performance in a baseball batting task was influenced by previous performance, and could be mediated by changes in attentional focus (as measured by secondary task performance).…”
Section: Discussionmentioning
confidence: 99%
“…A compelling body of literature has reported that experts show longer quiet eye durations than novices for a variety of motor skills, ranging from precision sports to surgery (for reviews, see Gonzalez et al, ; Rienhoff, Tirp, Strauß, Baker, & Schorer, ; Vickers, ; Wilson, Causer, & Vickers, ; for meta‐analyses, see Lebeau et al, ; Mann, Williams, Ward, & Janelle, ). For instance, Walters‐Symons, Wilson, and Vine () tested 18 experienced golfers (mean handicap 5.7) and 21 novices (no formal handicap), as they putted balls to a 10‐ft (i.e., 3‐m) distant hole. They found that the experienced golfers had longer quiet eye durations ( M = 1.9 s) than the novices ( M = 1.2 s).…”
Section: Introductionmentioning
confidence: 99%